Knowing Good, Doing Bad: Understanding Environmental Ethics from an Aristotelian Perspective - Smith, James (The Stellenbosch Socratic Journal, 2021)
Aristotle developed the notion of akrasia in his Nicomachean Ethics. Akrasia describes situations where people know that their actions will be unethical; nevertheless, they continue to do those actions. This paper discusses how akrasia is a helpful means of understanding human behaviour in the wake of the environmental crisis. People know that their behaviours are environmentally damaging; nonetheless, they continue to engage in those behaviours. This makes these environmentally damaging behaviours more akin to weaknesses of will than epistemic failures. Understanding human behaviours towards the environment as akratic is useful because Aristotle’s solutions to akratic behaviour can become tools to combating environmental destruction.